Slag Formation During Pilot-Scale Pressurised Entrained-Flow Gasification of Woody Biomass - Ma, Charlie (Luleå tekniska universitet, Energivetenskap, 2014)
Pressurised entrained‐flow gasification (PEFG) of sustainable woody biomass offers the opportunity for envi-ronmentally benign production of syngas that is suitable for synthesis of fuels and other chemicals. During the PEFG process, ash-forming matter in the fuel undergoes transformations. Slag formation is an important form of ash transformation that occurs inside a PEFG reactor. In most industrial-scale PEFG of coal, the ash-forming matter becomes predominately molten and flows down the side of the reactor wall to be continuously tapped and removed. The slagging behaviour of woody biomass fuels during PEFG is expected to be different to that of coal, due to significant differences in the amount, composition and reactivity of the ash-forming matter. The objective of this thesis study was to initiate the elucidation of slag formation during PEFG of woody biomass. This was carried out by obtaining and characterising ash deposits and slags from pilot-scale experimental cam-paigns. An oxygen-fired pilot-scale reactor (ETC Piteå, Sweden) was used for the study. A low reactor temperature (< 1200 °C) study was carried out with three different fuels fired in separate experimental campaigns: stem wood, bark and pulp mill debarking residue (PMDR). Deposits were taken from each of the campaigns from the reactor for chemical characterisation. The stem wood fuel resulted in very little deposit that exhibited only minor amounts of melt, or slag, formation with enrichment of Si. The bark and PMDR fuels resulted in larger amounts of deposits with greater amounts of melt formation that were also enriched in Si. It was found that silica-based fuel contaminants, e.g., quartz sand and feldspars, may have an important role in melt formation. Following on, high reactor temperature (> 1350 °C) experimental campaigns involving stem wood produced flowing slags that eventuated in blockages of the reactor outlet. These slags were also retrieved from the reactor and characterised. It was found that they likely comprised of products ...